Geschichte als Performance. - Hüchtker, Dietlind, author.
1 online resource (318 pages)
Keywords: "This study analyzes history as performance: as the interaction of actors, plays, stages and enactments. By this, it examines women's politics in Habsburg Galicia around 1900: a Polish woman active in the peasant movement, a Ukrainian feminist, and a Jewish Zionist. It shows how the movements constructed essentialistically regarded collectives, experience as a medially comprehensible form of credibility, and a historically based inevitability of change, and legitimized participation and intervention through social policy and educational practices. Traits shared by the movements included the claim to interpretive sovereignty, the ritualization of participation, and the establishment of truths about past and future"--